G33k
  • G33k
i needed to edit this question :p
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
chestercat
  • chestercat
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
Simplifying 4x2 + -9x + -9 = 0 Reorder the terms: -9 + -9x + 4x2 = 0 Solving -9 + -9x + 4x2 = 0 Solving for variable 'x'. Factor a trinomial. (-3 + -4x)(3 + -1x) = 0 Subproblem 1 Set the factor '(-3 + -4x)' equal to zero and attempt to solve: Simplifying -3 + -4x = 0 Solving -3 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -4x = 0 + 3 Combine like terms: -3 + 3 = 0
anonymous
  • anonymous
0 + -4x = 0 + 3 -4x = 0 + 3 Combine like terms: 0 + 3 = 3 -4x = 3 Divide each side by '-4'. x = -0.75 Simplifying x = -0.75 Subproblem 2 Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3 Solution x = {-0.75, 3} You can always share this solution 0 Share 0 Google+ See similar equations: | 16x^2+8x-3=0 | | 7(h+5)=-35 | | x^2-9x-10=0 | | 3w-11=-4 | | 85+5(x-17)=215 | | 8(x-8)+32=128 | | 8(4x+8)=288 | | 7(3x-12)=84 | | Z^5=4 | | 4(8-2x)=-40 | | 2+3=8 | | 6+7=72 | | 7+8= | | 5g-4=7 | | 3a=2a+2 | | -9(2k)=-36 | | 10x-11= | | 5p-(-13)=-28 | | 2(x-6)+2=4(x+2)-10 | | 6-5(3x-4)=-19 | | 8x-(3x+6)=29 | | 8x-(3x+6)=29a | | 4.2x-5.36=3.36-6.7x | | 4.2x-536=3.36-6.7x | | 5.3x-1.08=1.06-5.4x | | 1.6+.80x=2.85x+1.25x+.75 | | 1.6+.80x=2.85+1.25x+.75 | | 1.8+6y=11y-.20 | | -2+.33t=.40 | | 3a+15=3a+4 | | 3.5x+.50x=2x+4.5+3.5x | | 3y-2+y+30=8y+30-6y | | 6-4x=7x-9x+8 | | 4x+8=3x+6 | | 6x-21=-56+x | | -2.5=0.1s+3.8 | | 7x-14=5x | | x+.20x=12 | | x+.25x=12 | | 5n-0.16=-0.51 | | -8x-11x=76 | | 8x+10x=90 | | -4x+5=41 | | -57=7+8x | | 6x+5=-139 | | -27+5m=-27 | | 4y-9y=-95 | | 5p-(-13p)=-28 | | 2k+14=6k-22 | | 2x+1=32 | | r-0.2r=-6.4 | | 42=m+6m | | 3(x+6)=14 | | 2-4c=2c | | 5d=17.1 | | 16+2x=10x | | 3x=45 | | 4-m=2(3m-5) | | -(-9p+1)=-2(-9+6b) | | 4(-10m+2)-2=1-2m | | 4(2b+2)=-5(-2+7b) | | -24=4(5T+19) | | -4=9p-2(-2p+3) | | -5(6y)=-50 | | -4=-(1+9m)-6m | Equations solver categories Equations solver - equations involving one unknown Quadratic equations solver Percentage Calculator - Step by step Derivative calculator - step by step Graphs of functions Factorization Greatest Common Factor Least Common Multiple System of equations - step by step solver Fractions calculator - step by step Theory in mathematics Roman numerals conversion Tip calculator
anonymous
  • anonymous
did that help

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
ur welc

Looking for something else?

Not the answer you are looking for? Search for more explanations.